2014
DOI: 10.4097/kjae.2014.67.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pretreatment with intravenous palonosetron for propofol-remifentanil-based anesthesia in breast and thyroid cancer surgery: a double-blind, randomized, controlled study

Abstract: BackgroundWe postulated that palonosetron, a novel antiemetic agent, might have the effect of alleviating injection pain from propofol and rocuronium. A double-blind, controlled study was undertaken to evaluate the effect of palonosetron on injection pain during total intravenous anesthesia and postoperative nausea and vomiting (PONV) using propofol-remifentanil in breast and thyroid cancer surgery.MethodsSixty patients were randomly allocated to one of two groups. Before injection of propofol and rocuronium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…At present, propofol combined with opiates or propofol combined with inhaled anesthetics are commonly used in patients undergoing radical gastrectomy. Propofol anesthesia has a rapid effect but no analgesic effect, so it needs to be used in combination with other analgesic drugs (5,22). Remifentanil is a short-acting opioid analgesic with rapid onset of anesthesia, good analgesic effect but short duration of action (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, propofol combined with opiates or propofol combined with inhaled anesthetics are commonly used in patients undergoing radical gastrectomy. Propofol anesthesia has a rapid effect but no analgesic effect, so it needs to be used in combination with other analgesic drugs (5,22). Remifentanil is a short-acting opioid analgesic with rapid onset of anesthesia, good analgesic effect but short duration of action (13).…”
Section: Discussionmentioning
confidence: 99%
“…Due to environmental pollution, food safety issues, unhealthy lifestyle and other reasons, the incidence of gastric cancer shows a trend of rejuvenation and normality. Most gastric cancer patients receive preoperative chemotherapy, but chemotherapy drugs damage their liver, heart and kidney (5,6). Therefore, gastric cancer patients suffer from large trauma, severe pain and a series of severe stress responses during surgical treatment, as well as more complications after operation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Our result is supported by prior clinical studies. Pretreatment of palonosetron 0.075 mg could effectively reduce early postoperative pain after thyroid and breast cancer as well as propofol-induced injection pain [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the 5-HT 3 receptor is involved in the modulation of nociceptive transmission [ 21 ]. Lee et al [ 22 ] reported that the pain score in the palonosetron group was lower than that of the control group. In addition, in a previous study on the effects of dexamethasone on pain, administration of dexamethasone resulted in reduced pain score, length of hospital stay, and opioid consumption compared with control after total knee arthroplasty [ 23 ].…”
Section: Discussionmentioning
confidence: 99%